Isotopic Fractionation Associated With Sulfate Import and Activation by Desulfovibrio vulgaris str. Hildenborough - Smith, Derek A.; Fike, David A.; Johnston, David T.; Bradley, Alexander S. (Frontiers in Microbiology, 2020)
The use of stable isotopes to trace biogeochemical sulfur cycling relies on an understanding of how isotopic fractionation is imposed by metabolic networks. We investigated the effects of the first two enzymatic steps in the dissimilatory sulfate reduction network – sulfate permease and sulfate adenylyl transferase (Sat) – on the sulfur and oxygen isotopic composition of residual sulfate. Mutant strains of Desulfovibrio vulgaris str. Hildenborough with perturbed expression of these enzymes were grown in batch culture, with a subset grown in continuous culture, to examine the impact of these enzymatic steps on growth rate, cell specific sulfate reduction rate and isotopic fractionations in comparison to the wild type strain. Deletion of several permease genes resulted in only small (~1‰) changes in sulfur isotope fractionation, a difference that approaches the uncertainties of the measurement. Mutants that perturb Sat expression show higher fractionations than the wild type strain. This increase probably relates to an increased material flux between sulfate and APS, allowing an increase in the expressed fractionation of rate-limiting APS reductase. This work illustrates that flux through the initial steps of the dissimilatory sulfate reduction pathway can affect the fractionation imposed by the overall pathway, even though these steps are themselves likely to impose only small fractionations.